Analysis of The Effect of Region, Province and Breed on Somatic Cell Count in Dairy Cattle in Turkey By Regression Tree Method - Sahin, Onur (Emirates Journal of Food and Agriculture, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*53.79px); top: calc(var(--scale-factor)*261.97px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.05663);" role="presentation">This study aimed to determine the effect of various environmental factors on the somatic cell count (SCC) in cow’s milk. The material of <span dir="ltr" style="left: calc(var(--scale-factor)*53.79px); top: calc(var(--scale-factor)*271.97px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.06617);" role="presentation">the study consisted of an SCC analysis result obtained from 207.614 raw milk samples collected from 65.288 head cattle had different <span dir="ltr" style="left: calc(var(--scale-factor)*53.79px); top: calc(var(--scale-factor)*281.97px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.06676);" role="presentation">breeds, ages, lactation number, and lactation length between May and December in 2019. They were raised on 6,305 dairy farms that <span dir="ltr" style="left: calc(var(--scale-factor)*53.79px); top: calc(var(--scale-factor)*291.97px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.05689);" role="presentation">are members of the Cattle Breeders Association (CBAT). In order to determine the effect of region, city, and cattle breed on SCC in raw <span dir="ltr" style="left: calc(var(--scale-factor)*53.79px); top: calc(var(--scale-factor)*301.97px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.03952);" role="presentation">milk of cattle, a regression tree was created using the Chi-square Automatic Interaction Detection (CHAID) algorithm, a Data Mining (DM) <span dir="ltr" style="left: calc(var(--scale-factor)*53.79px); top: calc(var(--scale-factor)*311.97px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.07063);" role="presentation">method. Accordingly, the mean SCC value of all enterprises was determined as 201.253 <span dir="ltr" style="left: calc(var(--scale-factor)*390.28px); top: calc(var(--scale-factor)*311.97px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.10405);" role="presentation">cells/mL. In this study, it was found that the <span dir="ltr" style="left: calc(var(--scale-factor)*53.79px); top: calc(var(--scale-factor)*321.97px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.05961);" role="presentation">region, city and breed groups with the highest average somatic cell counts were CAR, MSR, MR and SAR region group (285.430 <span dir="ltr" style="left: calc(var(--scale-factor)*538.99px); top: calc(var(--scale-factor)*321.97px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.04478);" role="presentation">cells/<span dir="ltr" style="left: calc(var(--scale-factor)*53.79px); top: calc(var(--scale-factor)*331.97px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.08022);" role="presentation">mL); C09, C45, C20, C64, C48, C43 city group (266.744 <span dir="ltr" style="left: calc(var(--scale-factor)*271.35px); top: calc(var(--scale-factor)*331.97px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.04493);" role="presentation">cells/mL); and HF, MC, and BS breed group (295.705 <span dir="ltr" style="left: calc(var(--scale-factor)*470.74px); top: calc(var(--scale-factor)*331.97px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.05004);" role="presentation">cells/mL). As a result of <span dir="ltr" style="left: calc(var(--scale-factor)*53.79px); top: calc(var(--scale-factor)*341.97px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.06292);" role="presentation">this study, the variables affecting SCC were determined as region, city, and breed respectively, in order of importance. <span dir="ltr" style="left: calc(var(--scale-factor)*53.79px); top: calc(var(--scale-factor)*357.64px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.06341);" role="presentation">Keywords: <span dir="ltr" style="left: calc(var(--scale-factor)*96.15px); top: calc(var(--scale-factor)*357.64px); font-size: calc(var(--scale-factor)*8.00px); font-family: sans-serif; transform: scaleX(1.06079);" role="presentation">CHAID; Dairy cattle; Somatic cell count